2013
DOI: 10.1017/s0007114513002201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary lipid structure in early postnatal life on mouse adipose tissue development and function in adulthood

Abstract: Obese individuals have more (hyperplastic) and larger (hypertrophic) adipocytes in their white adipose tissue (WAT) than normal-weight individuals. The difference in cell number emerges early in childhood, suggesting that this is a critical period for being susceptible to obesity. Breast-feeding has been shown to be protective against obesity, and we have previously shown in mice that the physical structure of lipids in human milk may contribute to this protective effect. In the present study, we investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
89
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 61 publications
4
89
1
2
Order By: Relevance
“…Mice fed Concept IMF until early adulthood showed reduced adiposity when subsequently challenged by a moderately high-fat Western-style diet in adolescence and adulthood despite similar food intake [18,19]. These nutritional programming models using rodent pups [18,19] suggested that the altered lipid structure of the Concept IMF in early life affected adult adipocyte functionality but not adipocyte number. Also, the metabolic response to this diet was improved in Concept IMF-fed mice, with lower body weight and lower plasma insulin despite similar food intake.…”
Section: Introductionmentioning
confidence: 99%
“…Mice fed Concept IMF until early adulthood showed reduced adiposity when subsequently challenged by a moderately high-fat Western-style diet in adolescence and adulthood despite similar food intake [18,19]. These nutritional programming models using rodent pups [18,19] suggested that the altered lipid structure of the Concept IMF in early life affected adult adipocyte functionality but not adipocyte number. Also, the metabolic response to this diet was improved in Concept IMF-fed mice, with lower body weight and lower plasma insulin despite similar food intake.…”
Section: Introductionmentioning
confidence: 99%
“…At this stage, however, the fact that kinetics of lipid digestion could further modulate plasma TG appearance (Michalski et al, 2006) and b-oxidation rate (Michalski et al, 2005a) was already established in animal models and later on confirmed in human (Vors et al, 2013). In a further study (Oosting et al, 2014), still using a very close design study in mice, it was shown (2015) and Bourlieu et al (2015a).…”
Section: 1mentioning
confidence: 93%
“…Several meta-analyses have shown that breast-feeding has a small protective effect against obesity later in life (Agostoni et al, 2009). Relying on these positive outcomes and considering the strong difference of lipid structure between IF and HM, Oosting et al (2014) set the hypothesis that HM lipid structure was involved in programming.…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, milk fat emulsified by protein results in enhanced lipemia and higher b-oxidation (i.e., lower storage) than unemulsified fat (25). There is also evidence that PLs consumed early in development may have lasting effects on metabolism, because mice pups initially fed an infant formula composed of large lipid droplets coated with MPLs were then less susceptible to the deleterious effects of a high-fat diet, compared with infant formula that contained small lipid droplets coated with proteins (26,27). Collectively, these data indicate that PLs as emulsifiers may affect postprandial lipid trafficking via a mechanism involving differential digestive hydrolysis and that the composition and character of the PLs isolated from different sources may contribute to this process.…”
Section: Introductionmentioning
confidence: 99%